Self-efficacy and perceived barriers of pregnant women regarding exposure to second-hand smoke at home - Seyed Saeed Mazloomy Mahmoodabad; Zohreh Karimiankakolaki; Ashraf Kazemi; Hossein Fallahzadeh (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND and AIM: The inability of women to demand from their husbands, for not smoking, has been reported as a factor in exposure to cigarette smoke. This study aimed to investigate the perceived barriers and self-efficacy of pregnant women regarding second-hand smoke (SHS) at home. MATERIALS and METHODS: This was a cross-sectional study, and the sample size was 255 pregnant women who visited the health-care centers in Isfahan, Iran, from July 2018 to September 2018, and were selected randomly and voluntarily. A questionnaire was designed to collect the data about the exposure to smoke, perceived barriers, and self-efficacy. The data were analyzed using descriptive statistics (mean score and standard deviation), inferential statistics (nonparametric Mann-Whitney and Kendall test), and Spearman's correlation and regression. RESULTS: The mean score of self-efficacy in the exposure group was lower than that the other group (P = 0.000). The mean score of perceived barrier was not a significant difference (P = 0.449). Personal perceived barriers are the most important predictor of self-efficacy of pregnant women in exposure to SHS (95% confidence interval: 0.013-0.262) (P = 0.030). Kendall test comparing items within the group and Mann-Whitney test comparing the two groups showed that personal factors such as "Unaware of the dangers of SHS and protective measures" for notexposed women and environmental factor "the lack of ban smoking law at home" for exposed women are considered the most important barriers ( P = 0.000). "Not being together a husband" (P = 0.293) and "going to another place when smoking a husband" (P = 0.000) are the highest self-efficacy items. CONCLUSIONS: It is necessary to develop training programs to increase self-efficacy to avoid exposure to SHS and for both pregnant women and their husbands. It is also necessary to educate and inform about SHS and protective measures against it and to set up "smoking ban law" at home in our country to protect pregnant women.